STUDI EVALUASI KEAKTIFAN DAN KEUNGGULAN KOMPETITIF DAN KOMPARATIF SDM KONSTRUKSI TEKNISI/TENAGA TERAMPIL DI PROVINSI KALIMANTAN SELATAN - Zain Hernady Arifin; Reza Adhi Fajar (Universitas Lambung Mangkurat, 2015)
Human Resources in construction are individuals who practice the profession in engineering and kearsitekturan and skilled workers (labor skills) in the construction sector. ASEAN Free Trade Area (AFTA) will be applied. There will only be a single market and production base with five main elements, yatu free flow of goods, free services, free investment, capital flows and free flow of skilled labor. In fact only partially SDM active construction (the true players) while the rest just borrowed its name (the shadow players). In addition, it should also be known a real picture of how big comparative advantage and competitive advantage SDM Indonesian construction or area in order to face competition in the single market of the ASEAN (AFTA, 2015). Skilled Manpower local contribution is relatively moderate to increased construction services sector in the province of South Kalimantan. In this case the maximum effort must be taken of local communities in order to improve the construction services in the context of quality and quantity.This has resulted in much chance (opportunity) Skilled from outside the province or from outside the island. Skilled portrait in the province of South Kalimantan consecutive gradually decreases linearly with the level of education at Skilled qualification Tk 1, Tk.2 to Tk.3. There are several things that can be recommended for stakeholders to improve the system, namely: 1. Acceleration up-grading Skilled Local, supported by the Party Regulator construction services (Government and LPJK) more strict in applying the rules relating to the certification of skilled workers in the area. 2. The database for Skilled Workers, particularly at Level 2 qualification. 3. Level 3, where a database of skilled labor is easily accessible online and update. Keywords: Skilled, Construction, South Kalimantan